Clinicopathological features of plasmablastic multiple myeloma: a population‐based cohort. Issue 8 (8th July 2015) - Møller, Hanne E. H.; Preiss, Birgitte S.; Pedersen, Per; Kristensen, Ida B.; Hansen, Charlotte T.; Frederiksen, Mikael; Abildgaard, Niels; Møller, Michael B.
<x xml:space="preserve">Abstract</x> Multiple myeloma (MM) is a common malignant hematological disease displaying considerable heterogeneity. Historical data indicate a prognostic significance of plasmablastic morphology, proliferation, and adverse cytogenetics, but there is little knowledge on the degree of interdependency of these parameters. The aim of this study was to study the degree of overlap between these variables. In a consecutive population‐based cohort of 194 untreated MM patients, morphology, and proliferation index, using immunohistochemical double staining for Ki‐67 and CD138, was analyzed. In addition, cytogenetic changes were studied by karyotyping and fluorescence in situ hybridization (FISH). Plasmablastic morphology correlated with unfavorable clinical features, high proliferation index, high percentage of plasma cell infiltration in the bone marrow, abnormal karyotype, and del(13q) detected by karyotyping, which indicates that plasmablastic morphology reflects advanced and highly proliferative disease. However, plasmablastic morphology did not correlate with established adverse prognostic cytogenetics identified by FISH, for example, t(4;14), t(14;16) and del(17p).